A study of vocabulary learning strategies among pre-university ESL learners at IIUM - Gana, Mouna (Kulliyah of Education,International Islamic University Malaysia, 2021)
Insufficient vocabulary knowledge is a barrier that hinders learners to acquire a second language as it leads to incompetency in mastering all four language skills. However, in order to increase their vocabulary stock and master the second language, learners will need the right tools, in which among these tools are vocabulary learning strategies (VLSs). This study is aimed at exploring the types of vocabulary learning strategies and to determine the most and least used strategies for vocabulary learning among English language learners in a public university in Malaysia. A quantitative and qualitative mixed research method was employed in the study. In the first phase, data was collected using the vocabulary learning strategy questionnaire adapted from Schmitt (1997). The study sample for data collection consisted of 260 CELPAD students at IIUM Gombak which was obtained through purposeful sampling. SPSS software (version 22) was run to analyse the data using descriptive analysis. The results of the first phase showed that CELPAD students were “moderate” strategy users overall. With regard to strategy categories, the results revealed that memory strategies were the most frequently used and determination strategies were the least frequently used among the learners. In the second phase, was analysed through a semi-structured interview with four CELPAD students. The findings suggest that the participants actively invoke a variety of strategies in order to identify the meaning of unfamiliar words in their reading comprehension. Five emergent themes were found: dictionary use, guessing context, skipping, use of multiple sources, and note-taking strategy. To conclude, further research is recommended in various contexts regarding vocabulary learning strategies.